ImmunoPhysics and ImmunoEngineering - Bernardino De La Serna, Jorge; Mellado, Mario; Garcia-Parajo, Maria; Loran Dustin, Michael; Morikis, Dimitrios (Frontiers Media SA, 2020)
ImmunoPhysics (ImmPhys) and ImmunoEngineering (ImmPhysEng), are two cross-disciplinary fields. ImmPhysEng aims to unravel quantitatively the immune-system function and regulation in health and disease. Whereas ImmPhys study and assess the physical basis of the immune response, ImmEng pursues its control and prediction. Ultimately, the overarching goal of these disciplines is to facilitate the development of therapeutic interventions to more precisely modulate and control the compromised immune response during diseases. Lately, these disciplines are becoming more popular and as such, the number of publications applying physical or engineering tools to understand the immune response is increasing. Nevertheless, there is still no scientific forum compiling the ImmPhysEng research breakthroughs. Possibly the biggest burden is to stimulate a fluent communication and syntony between a physicist or engineer and an immunologist.